2010
DOI: 10.1099/ijs.0.018697-0
|View full text |Cite
|
Sign up to set email alerts
|

Halosarcina limi sp. nov., a halophilic archaeon from a marine solar saltern, and emended description of the genus Halosarcina

Abstract: Halosarcina limi sp. nov., a halophilic archaeon from a marine solar saltern, and emended description of the genus Halosarcina A halophilic archaeon, strain RO1-6 T , was isolated from a marine solar saltern in eastern China.Cells of strain RO1-6 T were pleomorphic and motile and stained Gram-negative. Strain RO1-6 T grew well on complex medium and colonies were red-pigmented. It was able to grow at 20-50 6C (optimum 37 6C), in 2.1-5.1 M NaCl (optimum 3.9 M NaCl), in 0.05-0.70 M MgCl 2 (optimum 0.30 M MgCl 2 )… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 18 publications
(17 reference statements)
0
13
0
Order By: Relevance
“…Prior studies have identified members of the Halorubrum and Haloquadratum and, in some samples, Halonotius, Natrinema, and Haloferax as dominant members of crystallizer salterns (8,45,47), while in our study, members of the recently described genera Halogranum, Halolamina, Halosarcina Halorientalis, and Haloplanus represented a major fraction of the Halobacteriales community in multiple habitats (e.g., 60.8, 66.4, 41.1, and 49.4% in MAN, ZDT, CAR, and SPL, respectively). This attests to the relevance and significance of recent efforts for the isolation and characterization of novel Halobacteriales genera in various habitats beyond typical hypersaline water bodies (14)(15)(16)(17)(18)(19)(20)(21)59). Unfortunately, aside from standard information presented in species description papers, little information is available regarding the physiological capabilities, adaptive mechanisms, and genomic characteristics of these genera.…”
Section: Figmentioning
confidence: 99%
See 2 more Smart Citations
“…Prior studies have identified members of the Halorubrum and Haloquadratum and, in some samples, Halonotius, Natrinema, and Haloferax as dominant members of crystallizer salterns (8,45,47), while in our study, members of the recently described genera Halogranum, Halolamina, Halosarcina Halorientalis, and Haloplanus represented a major fraction of the Halobacteriales community in multiple habitats (e.g., 60.8, 66.4, 41.1, and 49.4% in MAN, ZDT, CAR, and SPL, respectively). This attests to the relevance and significance of recent efforts for the isolation and characterization of novel Halobacteriales genera in various habitats beyond typical hypersaline water bodies (14)(15)(16)(17)(18)(19)(20)(21)59). Unfortunately, aside from standard information presented in species description papers, little information is available regarding the physiological capabilities, adaptive mechanisms, and genomic characteristics of these genera.…”
Section: Figmentioning
confidence: 99%
“…Halorientalis-affiliated sequences were abundant members (Ͼ5%) of the Great Salt Plains, mangrove, and Great Salt Lake sediments (Table 2). Finally, members of the genus Halosarcina were originally isolated from Zodletone Spring (59) and subsequently identified in Chinese salterns (21). Halosarcinaaffiliated sequences, however, represented only 2% of the Halobacteriales community at Zodletone Spring (Table 2) but were present in relatively high abundance in SPL and CAR samples.…”
Section: Diversity Patterns In Halobacteriales Communitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The description is identical to that of Halosarcina limi given by Cui et al (2010b). The type strain is RO1-6 T ( = CGMCC 1.8711 T  = JCM 16054 T ).…”
Section: Description Of Halogeometricum Limi Comb Novmentioning
confidence: 89%
“…The strains were routinely grown aerobically at 37 °C in NOM medium (Cui et al , 2011a). Phenotypic tests were performed according to the proposed minimal standards for description of new taxa in the order Halobacteriales (Oren et al , 1997).…”
mentioning
confidence: 99%